Reaksi Pasar Terhadap Divestasi Saham PT. Freeport Indonesia Ke PT. Inalum - Alpian Adi Herawan; Irianto Irianto; Baiq Kisnawati (Fakultas Ekonomi Universitas Islam Al-Azhar, 2019)
The capital market is one of the economic instruments for buying and selling securities in the form of shares and bonds. There are two parties in the capital market, those who need funds and those who have excess funds. There are several events that can affect abnormal return and trading volume activity, one of them is the announcement of the divestment of a company's shares. There is an economic event that is very attention-grabbing in 2018, namely the divestment of PTFI shares to PT Inalum. This event is considered as one of the information for investors who want to invest. This study aims to determine the differences in the average abnormal return and the differences in the average trading volume activity that occurr in the period before and after the announcement of the divestment of shares. This research is an event study research. The population and sample used in this study were members of the holding companies of Mining, namely ANTAM, TINS ​​and PTBA. Data analysis used is paired t test analysis. The test results obtained that there is no significant difference in the average abnormal return and average trading volume activity before and after the divestment event.